Analysis of dual fluidized bed gasification integrated system with liquid fuel and electricity products. (13th July 2016) - Chen, Hao; Zhang, Xiangping; Wu, Bin; Bao, Di; Zhang, Suojiang; Li, Jianwei; Lin, Weigang
Abstract: Dual fluidized bed (DFB) reactor is one of promising ways for biomass gasification. In this work, an integrated system is designed to produce multi products, i.e., liquid fuel and electricity using biomass as feedstock. The system consists of four main sections, i.e. Gasification, CO2 capture, F-T synthesis, Power Generation. HRSG unit is applied to recover the sensible heat and produce steam, and the heat and electricity demanded by this system are produced by itself. The simulation is conducted in Aspen Plus and the results are verified with the literature and industrial data. Carbon chain analysis, energy analysis and green degree method are applied to evaluate the mass conversion, energy utilization and environmental influence of the system, which presents a clear description of the whole system. Furthermore, CO conversion of DFB reactor has a significant influence on oil production. The results show that 39.7% (HHV) of biomass energy is stored in products, 24.0% (HHV) in liquid fuel and 15.7% (HHV) in electricity. The energy efficiency comparison between several integrated systems is also given. Highlights: DFB reactor is integrated into a system to produce liquid fuel and electricity. Carbon chain analysis, energy analysis and green degree method are applied to evaluate the system. Energy efficiency of several integrated systems are compared with this work.